A tri-level optimization model for a private road competition problem with traffic equilibrium constraints - Gu, Yan (2020)
The Build-Operate-Transfer (BOT) scheme is widely applied in many cities, wherein firms compete to invest in road building and aim to maximize their profits by collecting tolls from users traveling on the roads under their control. Previous research analyzing the private road competition problem assumed that all the new roads would be constructed and operated by private firms under the BOT scheme. The present study recommends a more proactive participation from the government in the new road construction and operation so as to ensure the fulfillment of social welfare. We characterize this problem into a tri-level optimization model. In such a multi-competition game, strategic interaction and market equilibrium must be taken into consideration to determine their investment (road capacity) and price (toll level). Game-theoretic approaches are applied when the toll road network is controlled by more than one private company. Then, we propose a heuristic approach to solve the model and its validity is justified by a simple network numerical example.